Cocaine detrimentally affects mitochondrial functionality and cell viability in dopaminergic neurons. - Zamorano-González, Pablo; Bandini, Luca; Valverde, Nadia; Claros-Gil, Silvia; Romero-Zerbo, Silvana Yanina; Lara, Estrella; Santín-Núñez, Luis Javier; Martín-Montañez, Elisa; Gago-Calderón, Belén; García-Fernández, María Inmaculada (My University, 2024)
An elevated consumption of cocaine (benzoylmethylecgonine), which causes anesthetic and stimulant effects on the central nervous system, may be associated with several neurodegenerative conditions affecting dopaminergic neurons, such as Parkinson's disease (PD). To investigate the impact of cocaine on cell viability and morphology, dopaminergic neurons from the substantia nigra (SN4741) were cultured. Analysis involved assessing cell death (LDH levels) and cell morphology (GIEMSA staining) after a 24-hour treatment period. Additionally, the effects on reactive oxygen species (ROS) generation (DH2), membrane potential (JC-1), oxygen consumption rate (OCR), and mitochondrial stress (Seahorse) were evaluated after a 6-hour treatment. The optimal concentration of cocaine for experimental use (2 mM) was identified, inducing a substantial 39.75% neuronal death. Examination of neuronal death (LDH) revealed a remarkable 280% increase following cocaine treatment. Optical analysis demonstrated heightened mortality and detrimental changes in neuronal morphology post-cocaine treatment, including a globose shape, loss of synapses, extremely thin membrane, and cell aggregation. In the "short time" experiments, mitochondrial oxidative damage was evident in SN cells treated with cocaine, leading to the demise of 75% of the cells. Furthermore, a significant 173.6% increase in reactive oxygen species (ROS) production and a 20% reduction in mitochondrial membrane potential (JC-1 assay) were observed. Cocaine treatment also resulted in a notable 60% decrease in mitochondrial oxygen consumption. In summary, a concentration of 2 mM cocaine induces a considerable rise in mitochondrial oxidative damage, subsequently causing morphological alterations and progressive death of dopaminergic neurons due to the accumulation of reactive oxygen species (ROS).
Keywords: Cocaína - Efectos fisiológicos; Sistema dopaminérgico; Cocaine; Dopaminergic neurons; Oxidative damage; ROS levels